Assessment of parents’ understanding of pediatric medical prescriptions - Dr Jatin Dhanani; Dr. Rameshkumar Dihora; Dr. Ashish Goti; Dr. Rima Shah (Pediatric Review: International Journal of Pediatric Research, 2020)
Objective: To assess the accuracy of the parent understanding of pediatric prescription and prescribed medications and examine factors associated. Methods: Cross-sectional, observational questionnaire-based study involving 354 eligible parents was carried out in the pediatric department of a tertiary care teaching hospital. Parent’s sociodemographic details and their understanding of prescription including medication name, indication, dose, frequency, and duration were assessed by a self-administered questionnaire and their association analyzed statistically. Results: Mean age of parents was 33 ± 1.2 with the majority of females 57.06%. Out of 354 parents, 22.32% had low literacy and 37.74% were working as farmers. Overall understanding of prescription was present in only 25.14% of parents. The majority of parents were having a better understanding of the frequency of drug administration (79.09), while poor understanding was observed with respect to dosage calculation of medication (45.76%) and adverse drug reactions (25.14%) and the difference in the understanding was statistically significant (P<0.05). Factors like the age of parents, Child’s age, parent occupation, education of parent, experience in administering medicine, number of medicines prescribed, and type of dosage form were significantly impacting parent’s understanding regarding medication (P<0.05). Conclusion: Unperceived medication instruction understanding gaps exist at all literacy levels for pediatric patients among all parents. Communication and care delivery practices need further evaluation. Practice implications: Clinicians should be aware of the frequency of parent medication misunderstanding and give more attention to parents’ counseling.